Evaluation of the accuracy of nine electronic apex locators by using Micro‐CT. (26th July 2017) - Connert, T.; Judenhofer, M. S.; Hülber‐J, M.; Schell, S.; Mannheim, J. G.; Pichler, B. J.; Löst, C.; ElAyouti, A.
Abstract: Aim: To determine the accuracy of locating the apical constriction using apex locators. Methodology: Extracted teeth were micro‐CT scanned preoperatively to localize the apical constriction. Electronic length measurements of 91 root canals were made using nine electronic apex locators (EAL) connected to a mounting model. Distances from the major foramen were recorded at each scale bar of the EALs, and a file was fixed in the canal at a position indicated by each EAL to be the apical constriction. A second micro‐CT scan was conducted, and distances from the file tip to constriction and major foramen were calculated for each EAL. The accuracy of EALs was determined with a tolerance of 0.1, 0.25, 0.5 and 1 mm, and the 95% confidence interval was used to compare the EALs. A rank analysis was performed in which measurements beyond the major foramen were considered as inaccurate. Results: Regardless of the type of teeth, there was no significant difference in the accuracy of determining the apical constriction and major foramen between the nine EALs within a tolerance of ±0.5 mm and 1 mm, but there was a significant difference for the tolerances of ±0.1 and 0.25 mm. The highest ranks close to the constriction (98% and 94%) and to the major foramen (86% and 73%) were observed in Dentaport ZX and Elements Diagnostic Unit, respectively. Overestimation of working length beyond the major foramen was observed in all EALs (5% to 71%) when the scale for the major foramen, as recommended by the manufacturers, was used. However, when the scale for the constriction was used, only 3% of the measurements were beyond the major foramen. Conclusion: Electronic apex locators were able to determine the apical constriction. Using EALs to determine the major foramen led to overestimation of the working length. Therefore, it may be recommended to use the EAL scale of the constriction.